The Hobbit, or, There and back again - Tolkien, J. R. R., 1892-1973, (John Ronald Reuel); Inglis, Rob (New York : Recorded Books, 1997)
Here is Bilbo Baggins, the hobbit, thrust into myriad fantastic adventures by the wizard of Gandalf, finding within himself astonishing strength and courage in the face of danger.
Unabridged.
Dramatization.
Compact disc.
Performed by Rob Inglis.
Keywords: Middle Earth (Imaginary place) -- Fiction; Talking books; Gandalf (Fictitious character) -- Fiction; Hobbits (Fictitious characters) -- Fiction; Fantasy fiction